A deteriorating inventory model for determining optimal replenishment run time with failure rework and shortage. Issue 1 (2nd January 2021) - Sekar, T.; Uthayakumar, R.
Abstract : Many researchers focused on economic production quantity model for defective/deteriorating items under the assumptions (a) all the defective items can be reproduced as serviceable items (b) all the deteriorating items can be detached from inventory through screening process (c) shortages are not permitted. In an actual manufacturing environment, due to controllable or uncontrollable factors, some of the defective items may not be reproduced as serviceable items and due to human error or other factors, the internally deteriorated items may pass on to customers which will make negative impact on corporate image. This paper investigates an imperfect production inventory model with imperfect inspection of deteriorating items and failure rework under finite planning horizon. This system consists of m replenishment runs with failure rework and shortage. The main objective is to determine the optimal replenishment run time, optimal economic production quantity and optimal replenishment cycle time with the aim of minimising the total cost of the model. A solution procedure with an algorithm is proposed and a numerical example is provided to the theoretical results and to highlight the managerial insights.